Czechoslovak People’s Party and the Issue of Recognizing the USSR in February–April 1927 (According to the Documents of the Soviet Plenipotentiary Representation in Prague) - Nikolay N. N. Stankov (Historia provinciae: журнал региональной истории)
Referring to the documents of the Archive of Foreign Policy of the Russian Federation, the author of the article examines the approach of the Czechoslovak People’s Party to the recognition of the Soviet state and the motivation of the former in that matter. The article shows that the first statement made by the party’s leadership on the recognition of the USSR was the speech delivered by Mngr. F. Světlík (canon of the Olomouc Diocese, deputy of the National Assembly of the Czechoslovak Republic from the Czechoslovak People’s Party) in the Parliamentary Commission on Foreign Affairs on February 11, 1927. Advocating rapprochement with Moscow, Světlík and his supporters proceeded from the economic interests of their country and counted on the softening of the Bolsheviks’ revolutionary ideology and the expansion of the Catholic Church’s activities in the USSR. The author considers in detail the discussion in the Czechoslovak People’s Party and the response of other political forces in the Czechoslovak Republic to Světlík’s speech. Considerable attention is paid to the study of the activities conducted by the Soviet plenipotentiary representation in Prague in order to establish contacts with the Catholic circles of the Czechoslovak Republic and neutralize the publications in the Czechoslovak press about the anti-religious policy of the Soviet government and persecution of believers in the USSR, for which the plenipotentiary representation widely used the book Church Life in Moscow by Jesuit M. d’Herbigny, director of the Pontifical Oriental Institute. In the final part of the article, the author notes the reasons why the Czechoslovak People’s Party was unable to take the initiative and influence the decision of the state to recognize the USSR de jure in 1927 despite its status as a government party. Among those reasons were regional disunity of the party, disagreements in its leadership, significant dependence on the domestic and international political situation, and continued persecution of the Catholic clergy in the Soviet Union. Under such circumstances, the efforts of Soviet diplomats to encourage the leadership of the Czechoslovak People’s Party to initiate the recognition of the USSR de jure were doomed to failure.